2022
DOI: 10.1039/d2qm00880g
|View full text |Cite
|
Sign up to set email alerts
|

Single-atom substitution in donor–acceptor covalent organic frameworks for tunable visible light photocatalytic Cr(vi) reduction

Abstract: Hexavalent chromium (Cr(VI)) is hazardous and harmful to human health and the ecological environment. Photoreduction of high toxic Cr(VI) to low toxic Cr(III) by visible light is a low-cost and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…However, reports about benzoselenadiazole COFs are sporadic so far. 39–41 Hitherto, there have been no reports about benzoselenadiazole COFs for selective oxidations. The robustness of photoactive benzoselenadiazole could be preserved in COFs even under the attack of ROS to explore their application in photocatalytic oxidations.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports about benzoselenadiazole COFs are sporadic so far. 39–41 Hitherto, there have been no reports about benzoselenadiazole COFs for selective oxidations. The robustness of photoactive benzoselenadiazole could be preserved in COFs even under the attack of ROS to explore their application in photocatalytic oxidations.…”
Section: Introductionmentioning
confidence: 99%
“…[98][99][100] MOFsor COFs-based photocatalysts have been respectively applied for the photocatalytic selective reduction of metal species such as Cr(VI) and U(IV) in recent years. [101][102][103][104][105] Recently, Hu et al reported that the constructed NH 2 -MIL-125(Ti)@TpPa-1 heterojunction via Schiff base exhibited 81.6% photoreduction removal rates of U(VI), much higher than 57.7% of NH 2 -MIL-125(Ti) in photoreduction because of the broadened visible light response and improved separation of photogenerated carriers. 106 The photogenerated electrons and O 2 À radicals were demonstrated to be the primary reductive radicals while OH radicals had some negative influence on U(VI) reduction.…”
Section: Photocatalytic Selective Reductionmentioning
confidence: 99%
“…29,30 Since the discovery of heterogeneous photocatalysis over semiconducting COFs by Jiang and co-workers, 31 COF-based materials have been widely used in diverse photocatalytic elds, such as water splitting, 32,33 CO 2 reduction, 34,35 organic synthesis 36,37 and environmental remediation. [38][39][40] COF-based photocatalysts have several advantages compared to other inorganic photocatalysts: (i) the dened structure-property relationship in COFs is favourable for modication; (ii) COFs have higher specic surface areas, resulting in hundreds or even thousands of active sites; (iii) COFs have good crystallinity, which ensures their stability and signicantly reduces the electron-hole recombination frequency; (iv) the periodically ordered columnar array of the p-p-conjugated system facilitates electron delocalisation and endows COFs with excellent electron transport properties and photoconductivity; and (v) the designability of the donor-acceptor structure and introduction of suitable building blocks facilitate electron-hole separation and enhance the photocatalytic performance of COFs. [41][42][43][44][45] Most COFs rely on loaded metals, such as Pt, Ir, and Re, to enhance their photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%